Success factors in football: an analysis of the German Bundesliga - Lepschy, H.; Wäsche, H.; Woll, A. (International Journal of Performance Analysis in Sport, 2020)
Knowledge of success factors in professional football is critical. However, the identification of the success factors primarily focused on English and Spanish leagues. In this paper, three seasons of the German Bundesliga (2014/2015 until 2016/2017) with a total of 918 matches were analysed. To facilitate a more precise analysis of success factors, only close matches were included and the home and away team perspective was analysed separately. Therefore, 29 variables were included in a generalised ordered logit approach. The results showed that defensive errors, market value, goal efficiency, shots from counter attacks, shots on target and total shots have the greatest impact. Furthermore, crosses showed a negative relationship with success. Besides, the opponent and home advantage are important contextual effects. Overall, 11 and 12 variables are significant, respectively. Duel success is only significant for away teams and a higher market value seems to have a more positive impact for them. This study provides novel data and contributes to prior results from other European leagues. Future research should further investigate the impact of ball possession and distance covered. Coaches should focus on accuracy rather than on quantity as well as train fitness (physically and mentally) to lower the risk of errors.